Separation of some vitamins in reversed-phase thin-layer chromatography and pressurized planar electrochromatography with eluent containing surfactant - Beata Polak (Nature Portfolio, 2021)
Abstract The separation of some water- and fat-soluble vitamins via micellar systems of reversed-phase high-performance thin-layer chromatography (HPTLC) and pressurized planar electrochromatography (PPEC) was subjected to research. Hence, the influence of the mobile phase composition (surfactant and acetonitrile concentration, eluent buffer pH) on the migration distances and zone separation of some vitamins (thiamine, riboflavin, niacin, pyridoxine, cyanocobalamin, folic acid, ergocalciferol and α-tocopherol) was investigated. Our results indicated that the applied technique has an impact on the solute order. Comparing the system capacity of HPLC and PPEC (measured as height of the theoretical plate) for the mobile phase systems with and without surfactant shows differences, especially for fat-soluble vitamin. The variances and reproducibilities (% RDS) values of the vitamin are less in PPEC than in TLC. Moreover, the migration distances of water-soluble vitamins are longer than fat-soluble ones. Overall, eluent consisting of 50% acetonitrile, 18.75 mM SDS, the buffer of pH 6.99 via the PPEC technique was most appropriate for determining the investigated vitamins in the artificial mixture and the two commercially available vitamin combinations.